Google Earth Engine Application on CoastSat for Shoreline Extraction - Limlahapun, Ponthip; Thongua, Pinmukda; Phaithaisong, Kanyanat (2022 12th International Conference on Software Technology and Engineering (ICSTE), 2022)
Coastal areas are subject to dynamic threats due to nature, e.g., wind, waves, coastal storms, sea-level rise, and human activity. The consequences may interfere with human activities such as aquaculture, tourism, and infrastructure. The shoreline along the Krachai subdistrict of Chantaburi Province in Thailand was monitored using satellite-based images from 2014-2022. The aim of this research is to apply CoastSat and Google Earth Engine to monitor shorelines. Using satellite imagery, we can observe and analyze coastlines over time with actual, reliable images in context. To save time, the methodology applied Python software programming based on Google Earth Engine to automatically search satellite datasets and study areas to avoid downloading a whole image. Accuracy was verified using visual interpretation and distance differences were calculated showing an average of 0.25 meters. The shoreline detected from CoastSat was clear and gave positive results, compensating for operational time, starting from satellite images received for shoreline detection. The CoastSat approach can be applied anywhere detectable by satellite. Slight changes cause difficulty showing these as printed material; therefore, a web-based solution was developed to allow users to select areas of interest.